Challenges in diagnosing schwannoma mimicking thyroid neoplasms on frozen section - Ramadhani, Rahmi; Mayorita, Pamelia; Asri, Aswiyanti; Mulyani, Henny; Novianti, Hera (Institute of Computer Science (IOCS), 2025)
Schwannoma is a benign soft tissue tumor of the nerve sheath, composed of neoplastic cells with Schwann cell differentiation. It predominantly arises from peripheral nerves in the head, neck, and extremities, with a peak incidence in the fourth to sixth decades. Schwannoma is typically a solitary and sporadic lesion, affecting individuals of all ages, with an incidence rate of 4.4-5.23 cases per 100,000 people. The prevalence is around 7% of all primary nervous system tumors, often occurring in the head and neck (20-50%) and affecting cranial nerves such as N. Vagus and N. Sympathetic. This case report involves a 50-year-old female patient presenting with a right neck lump that had been present for 23 years, initially small but growing rapidly in the last 10 years with occasional pain. Initial imaging suggested a thyroid complex cyst, but further investigation, including a CT scan and intraoperative frozen section examination, raised suspicion for a malignant thyroid tumor. However, histopathological analysis confirmed the diagnosis of Schwannoma, distinguishing it from other potential malignant lesions, such as Anaplastic Thyroid Carcinoma (ATC). This case highlights the importance of intraoperative cytology and frozen section techniques for diagnosing Schwannoma. Although Schwannomas share morphological similarities with other tumors, particularly in the thyroid region, a multidisciplinary approach combining clinical, radiological, and histopathological findings is essential for an accurate diagnosis. This case also underscores the need for careful differential diagnosis in nerve sheath tumors located in the neck.